Corporate Social Responsibility (CSR) as an Instrument of Economic Justice - Berilian Ayu Kusuma; Sri Wahyuni Jumadi; Pramidazzura Alifa Rifqi (PT. Anagata Sembagi Education, 2025)
This study examines Corporate Social Responsibility (CSR) as a strategic instrument for achieving economic justice in the context of global corporate transformation. The research adopts a qualitative descriptive approach focusing on the economic institutional framework to analyze how CSR contributes to redistributive mechanisms, economic empowerment, and inclusive growth. Data were collected through semi-structured interviews with CSR managers from multinational companies in the energy, mining, and manufacturing sectors, complemented by secondary data from sustainability reports and global policy documents such as those by the OECD, UNDP, and GRI. The findings reveal that CSR has shifted from philanthropic activities toward a strategic economic mechanism capable of reducing inequality and fostering social inclusion. Firms that integrate CSR into their core economic strategy exhibit higher levels of supply chain resilience, stakeholder trust, and community welfare. The study also highlights that empowerment-based CSR programs, particularly those supporting local entrepreneurship and inclusive digitalization, significantly improve community income and business performance. Furthermore, CSR is found to drive long-term corporate transformation through sustainability-oriented innovation and stakeholder capitalism, aligning business profitability with distributive justice and institutional resilience. In conclusion, CSR functions not only as a moral obligation but also as a redistributive economic policy tool essential for achieving sustainable and equitable growth in the global economy.